A TREE SPECIES INVENTORY IN A ONE-HECTARE PLOT AT THE BATANG GADIS NATIONAL PARK, NORTH SUMATRA, INDONESIA - Kartawinata, Kuswata; Samsoedin, Ismayadi; Heriyanto, M; Afriastini, JJ (REINWARDTIA, 2004)
KARTAWINATA, KUSWATA; SAMSOEDIN, ISMAYADI; HERIYANTO, M. AND AFRIASTINI, J. J. 2004. A tree species inventory in a one-hectare plot at the Batang Gadis National Park, North Sumatra, Indonesia. Reinwardtia 12 (2): 145 â 157. The results of the inventory of trees with DBH = 10 cm shows that 184 species in 41 families, represented by 583 individuals with the total basal areas of 40.56 mÂ² occurred in the one-hectare plot sampled. Together with the saplings and shrubs the number of species was 240 belonging to 47 families. The forest is richer in tree species than other lowland forests in North Sumatra, but poorer than those in Borneo and the Malay Peninsula. Dipterocarps constituted 18.42 % of total species with basal area of 18.99 mÂ² or 46.82 % of the total basal area in the plot. The most prominent species was Shorea gibbosa. Hopea nigra, reported to be rare in Bangka and Belitung, occurred here as one of the ten leading species. The species-area curve shows that a considerable number of additional species was encountered more or less steadily up to one hectare and there was no indication of levelling off. A simulated profile diagram shows the forest may be stratified into five layers: (1) emergent layer, (2) upper canopy, (3) middle canopy, (4) lower canopy and (5) ground canopy. Dipterocarps were leading species in the emergent layer, upper canopy and middle canopy. Only 82 species were regenerating as represented by their presence in the sapling stage ranging from 5 to 50 plants/hectare. Macaranga lowii King ex Hook. f. dominated the section which seemed to be previously occupied by gaps.